2018
DOI: 10.7717/peerj.4970
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal and bacterial diversity and community composition from 18 phylogenetically divergent sponge species in Vietnam

Abstract: Sponge-associated prokaryotic diversity has been studied from a wide range of marine environments across the globe. However, for certain regions, e.g., Vietnam, Thailand, Cambodia, and Singapore, an overview of the sponge-associated prokaryotic communities is still pending. In this study we characterized the prokaryotic communities from 27 specimens, comprising 18 marine sponge species, sampled from the central coastal region of Vietnam. Illumina MiSeq sequencing of 16S ribosomal RNA (rRNA) gene fragments was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 106 publications
(150 reference statements)
4
53
0
Order By: Relevance
“…Despite methodological differences, the results from different approaches characterizing 16S rRNA gene profiles are highly reproducible, yielding detection differences only in low-abundance phyla such as Fusobacteria, Parcubacteria, PAUC34f, Hydrogenedentes and Saccharibacteria (Figure 2), some of which are part of the recently described candidate phyla radiation (Brown et al, 2015). These results are in accordance with other 16S rRNA gene based investigations, indicating that these methods are well established for molecular profiling of sponge microbiomes (Thomas et al, 2016;Chaib De Mares et al, 2017;Steinert et al, 2017;Dat et al, 2018). The vast majority of the abundant microbial taxa are detectable with both methods (overlap).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Despite methodological differences, the results from different approaches characterizing 16S rRNA gene profiles are highly reproducible, yielding detection differences only in low-abundance phyla such as Fusobacteria, Parcubacteria, PAUC34f, Hydrogenedentes and Saccharibacteria (Figure 2), some of which are part of the recently described candidate phyla radiation (Brown et al, 2015). These results are in accordance with other 16S rRNA gene based investigations, indicating that these methods are well established for molecular profiling of sponge microbiomes (Thomas et al, 2016;Chaib De Mares et al, 2017;Steinert et al, 2017;Dat et al, 2018). The vast majority of the abundant microbial taxa are detectable with both methods (overlap).…”
supporting
confidence: 84%
“…To date, more information on the in vivo conditions of the mesohyl habitat have become available through physiological tests and multi-omics tools. For example, temporarily anoxic parts occur during non-pumping periods (Hoffmann et al, 2005(Hoffmann et al, , 2008, and numerous nitrogen cycling-related genes and taxa suggest nitrogen cycling to be an important process within the sponge (Bayer et al, 2008;Dat et al, 2018). Additionally, complex carbohydrates forming the extracellular matrix of sponge mesohyl might represent an energy-source degradable by many symbionts (Kamke et al, 2013;Fiore et al, 2015;Bayer et al, 2018;.…”
Section: Culturing the Uncultivatedmentioning
confidence: 99%
“…Dominance of this archaea species has also been recorded in a calcareous sponge (Lopes et al, 2019), in several Antarctic sponges (Rodríguez-Marconi et al, 2015), and in three Ircinia species and Mycale laxissima from the Mediterranean and Caribbean seas (Zhang et al, 2014). C. Nitrosopumilus was also highly abundant in other 18 sponges from the same region in Vietnam amplified with bacteria primers (Dat et al, 2018). These authors found many aerobic nitrifiers among both symbiotic bacteria and archaea [C. Nitrosopumilus (AOA), Nitrosococcus, Nitrosomonadaceae (AOB), and Nitrospira (NOB)] and pointed out the putative relevance of aerobic nitrification in those sponges.…”
Section: Sponge Archaeal Communitiesmentioning
confidence: 82%
“…These authors found many aerobic nitrifiers among both symbiotic bacteria and archaea [C. Nitrosopumilus (AOA), Nitrosococcus, Nitrosomonadaceae (AOB), and Nitrospira (NOB)] and pointed out the putative relevance of aerobic nitrification in those sponges. In addition to C. Nitrosopumilus, we also retrieved members of Cenarchaeaum, which had not been previously detected in the Vietnamese species (Dat et al, 2018). Particulary, ZOTU2, affiliated to Cenarchaeaum, was consistently found in all the sponge samples studied, although it was solely abundant in Haliclona sp., where it accounted for more than 50% of the archaea relative abundance.…”
Section: Sponge Archaeal Communitiesmentioning
confidence: 99%
“…To date, enzyme inhibitors have received increasing attention, not only for discovery of their structures and action mechanisms but also for potential application in different fields 1,3 . Marine sponges are known to harbor diverse microbial communities [4][5][6] and represent a prolific source of natural products from their associated microorganisms [7][8][9][10] . Recent studies have shown that many potential protease inhibitors have been isolated from sponge-associated microorganisms [11][12][13][14] ; however, the exploration and exploitation potential PIs from microorganisms are still a big challenge because almost all microorganisms are resistant to cultivation in laboratory conditions, especially symbiotic microbes.…”
Section: Introductionmentioning
confidence: 99%